2022
DOI: 10.1097/mog.0000000000000894
|View full text |Cite
|
Sign up to set email alerts
|

Double-edged sword: impact of fecal microbiome transplants on the gut resistome

Abstract: Purpose of reviewFecal microbiome transplants (FMT) show promise in treating various diseases, such as Clostridioides difficile infections. FMT have also demonstrated the capacity to modulate the collection of antibiotic resistance genes (ARGs), termed the resistome, within the gut. The purpose of this review was to critically evaluate the literature regarding the interaction between FMT and the gut resistome and determine whether FMT could be used specifically to reduce ARG carriage in the gut. Recent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We did not perform shotgun metagenomic sequencing on the donor material from the FMT group, so could not ascertain if the ARGs are being introduced by the FMT. However, reports of the effects of FMT on ARG numbers have been heterogeneous ( 23 ). In previous studies, even after extensive screening of donor stool, FMT administration was the source of an antibiotic-resistant E. coli bacteremia ( 24 ), while Leung and colleagues ( 21 ) have reported that FMT may be a source of clinically relevant ARGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not perform shotgun metagenomic sequencing on the donor material from the FMT group, so could not ascertain if the ARGs are being introduced by the FMT. However, reports of the effects of FMT on ARG numbers have been heterogeneous ( 23 ). In previous studies, even after extensive screening of donor stool, FMT administration was the source of an antibiotic-resistant E. coli bacteremia ( 24 ), while Leung and colleagues ( 21 ) have reported that FMT may be a source of clinically relevant ARGs.…”
Section: Discussionmentioning
confidence: 99%
“…FMT may also be a strategy for decolonizing intestinal AROs where eradication rates have ranged from 37.5% to 87.5% in mostly small observational studies lacking a placebo control ( 18 ). However, there is inconclusive evidence that FMT is associated with decreases in antimicrobial resistance genes (ARGs) ( 23 ). Two studies demonstrated a decrease in overall ARGs ( 20 ) and patient-specific ARGs ( 22 ), while another study has shown that FMT is a potential source of ARGs ( 21 ).…”
Section: Introductionmentioning
confidence: 99%